Strontium-polyphenol composition and application of strontium-polyphenol composition in diabetic wound repair medical apparatus and instruments

Through metal polyphenol networks (SrC-MPNs) composed of strontium ions and chlorogenic acid, the problem of difficulty in healing diabetic wounds is solved, and effective repair and improvement of wounds is achieved.

CN119896652APending Publication Date: 2025-04-29SHANGHAI NINTH PEOPLES HOSPITAL SHANGHAI JIAO TONG UNIV SCHOOL OF MEDICINE
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202311401817.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-26
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The wounds of diabetic patients are difficult to heal, and existing treatments have problems with antibacterial resistance, unstable biological activity and potential adverse effects on the human body.

Method used

Metal polyphenol networks (SrC-MPNs) composed of strontium ions and chlorogenic acid are prepared by hydrothermal method to form a stable network structure and are loaded into a hydrogel to make a microneedle patch for wound repair.

Benefits of technology

SrC-MPNs@MN-PP significantly improves the microenvironment of diabetic wounds, has antibacterial, antioxidant, promotes angiogenesis and improves healing effects, and has good mechanical strength and biocompatibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119896652A_ABST
    Figure CN119896652A_ABST
Patent Text Reader

Abstract

The composition is of a network structure and is composed of strontium ions and chlorogenic acid, and the weight ratio of the strontium ions to the chlorogenic acid is 1: (9-11). The composition and hydrogel are mixed to prepare a microneedle patch, and the microneedle patch is prepared into a medical instrument for wound repair. Through verification, the SrC-MPNs is continuously released by the SrC-MPNs (at) MN-PP, so that the substances are dissolved and absorbed into tissue fluid around a wound, and strontium ions and chlorogenic acid in the SrC-MPN can stably and continuously exert the effects of resisting bacteria and oxidation, promoting angiogenesis, promoting wound healing and the like. An in-vivo experiment result shows that the SrC-MPNs (at) MN-PP can promote in-vivo and in-vitro wound healing, promote M2 macrophage polarization, remove excessive ROS and promote angiogenesis and tissue regeneration so as to promote healing of diabetic wounds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a biomaterial, in particular to a network composition containing strontium ions and polyphenol compounds, and its application in repairing diabetic wounds and preparing medical devices. Background Art

[0002] Diabetes is a serious public health problem affecting millions of patients with high morbidity and mortality. By 2040, the number of diabetes cases is estimated to reach 642 million. Diabetic hyperglycemia can lead to multiple systemic complications, causing extensive local lesions in the wound microenvironment, including chronic inflammation, bacterial infection, angiogenesis disorders, and excessive accumulation of ROS, ultimately leading to delayed or non-healing of wounds. In severe cases, this can lead to amputation, sepsis, and even death. Therefore, there is an urgent need for a new treatment to address the problem of delayed or non-healing wounds in diabetic patients, which is a major problem in today's treatment.

[0003] In clinical practice, silver ions, chitosan, and bioactive dressings are often used to treat diabetic wounds. For example, silver ion dressings are very effective in in vitro antibacterial effects, but little is known about their toxicity to humans or potential adverse effects on humans. Studies have found that chitosan dressings have certain safety, biocompatibility, antioxidant, and antibacterial properties, but the bioavailability of chitosan requires its solubility in water or other solutions, which limits its widespread application. In addition, there are some bioactive dressings that can be anti-inflammatory and promote regeneration, but they are resistant. In previous preliminary studies, γ-PGA combined with Ceffe as a dressing for the treatment of diabetic wounds showed good efficacy and biosafety.

[0004] In addition, γ-PGA is also used to prepare soluble microneedles for the treatment of diabetic wounds and hair regeneration. It has a sustained release effect on drugs and has good mechanical strength and regeneration function. In addition, we also studied that ε-PLL has antibacterial activity and good biological activity, and combined γ-PGA and ε-PLL through physical interactions between ions to obtain an adhesive hydrogel γ-PGA / ε-PLL (PP) dressing. When PP is used in burn wounds and tracheal mucosal repair, it can absorb tissue fluid around the wound, adhere to the wound, form an isolation barrier, and promote tissue regeneration. On this basis, it is believed that a single treatment method cannot completely solve the problem of chronic wounds.

[0005] Currently, antibiotics, cytokines, and anti-inflammatory drugs are commonly used to treat diabetic wounds. Antibiotics that produce resistance; cytokines (such as VEGF and bFGF) promote angiogenesis, but their limited absorption through the skin and low in vivo stability limit their application. Anti-inflammatory drugs such as Chinese herbal medicines have good anti-inflammatory and antioxidant effects, but their biological activity is not stable. Chlorogenic acid is reported to be a natural plant extract with a wide range of sources and an important bioactive dietary polyphenol with many important biological activities (such as anti-inflammatory, antioxidant and antibacterial). It has multiple antibacterial effects and is suitable as an ideal preservative and food additive to replace synthetic antibiotics, thereby reducing the cost of medicine. However, the ortho-diphenolic hydroxyl group in its molecular structure is easily oxidized, and heat and light can lead to the loss of its biological activity, which limits its wide application. In addition, metal ions are essential trace elements for the human body, such as Mg 2+ 、Zn 2+ , Cu 2+ and Sr 2+ etc. Sr. 2+ It promotes the proliferation and migration of endothelial cells and fibroblasts, and secretes angiogenesis-related factors. When the strontium content in the human body is high, this can lead to strontium accumulation in the body and the formation of high blood strontium levels, which can lead to adverse consequences. Previous studies have found that gallic acid and curcumin combine with magnesium ions to form a metal polyphenol network that is thermally stable and bioactive, and can slowly release metal ions and drugs, regulate inflammation, antioxidant activity, and promote angiogenesis. This provides a reference for solving the problem of drugs with unstable bioactivity. Summary of the invention

[0006] One object of the present invention is to provide a composition, which is composed of strontium ions and polyphenol compounds, has a metal polyphenol network structure, has a stable structure, and can improve the diabetic negative microenvironment after acting on the wound surface.

[0007] Another object of the present invention is to provide a composition composed of strontium ions and polyphenol compounds, having a metal polyphenol network structure, a stable structure, antibacterial and antioxidant effects, and can promote angiogenesis after acting on the wound surface.

[0008] Another object of the present invention is to provide a composition, which is composed of strontium ions and polyphenol compounds to form a network structure, which is then loaded in a gel to form a microneedle patch, which is beneficial to promoting the repair of diabetic wounds.

[0009] Another object of the present invention is to provide a composition which can be used as an active ingredient to prepare medical devices to facilitate wound repair.

[0010] A fifth object of the present invention is to provide a medical device comprising a network structure composed of strontium ions and polyphenol compounds, which is used for wound repair, especially for repairing difficult-to-heal wounds.

[0011] A composition is composed of metal ions and polyphenol compounds in a network structure, specifically composed of strontium ions and chlorogenic acid, and the weight ratio of strontium ions to chlorogenic acid is 1:9-11.

[0012] The composition of the present application is prepared by hydrothermal method from Sr(NO3)2 and chlorogenic acid. Chlorogenic acid and strontium ions interact to form strontium polyphenol network (denoted as: SrC-MPNs), which has stable structure and has biological activities such as antibacterial, antioxidant, angiogenesis promotion and improvement of negative microenvironment of diabetes. For example, Sr(NO3)2 and chlorogenic acid are dissolved in water, stirred until uniform, pH=7 is adjusted, and after several hours (for example: 24 hours) in a 75°C water bath, centrifuged (for example: 12,000rpm), the composition is obtained.

[0013] Another composition, in which SrC-MPNs are loaded into a hydrogel, is not only beneficial for the SrC-MPNs to act and remain on the wound surface, but also beneficial for the delivery of SrC-MPNs and the controlled release of SrC-MPNs, such as delaying the release of SrC-MPNs or adjusting the release cycle of SrC-MPNs.

[0014] Suitable hydrogels for use in the composition of the present invention include, but are not limited to, PEG, PLGA-PEG, γ-PGA, ε-PLL, hyaluronic acid, gelatin, chondroitin sulfate and cross-linked modified derivatives thereof, such as, gels suitable for photo-crosslinking, such as GelMA, HAMA and γ-PGA / ε-PLL (PP), etc.

[0015] After the composition of the present invention is mixed with the hydrogel, it is added into a microneedle mold for shaping and then demolded to obtain a microneedle patch loaded with SrC-MPNs, which is recorded as: SrC-MPNs@MN.

[0016] When SrC-MPNs are mixed with a hydrogel made of γ-PGA / ε-PLL (e.g., weight ratio of 1:1) to form a microneedle patch, the patch can fall off on its own as the wound heals. It not only isolates the wound, but also makes it easier to remove the microneedles after the wound heals, and can also indicate whether the wound has healed.

[0017] Another composition is a microneedle patch (MN), including a network structure composed of strontium ions and polyphenol compounds, γ-PGA and ε-PLL, denoted as: SrC-MPNs@MN-PP, wherein the weight ratio of γ-PGA to ε-PLL is 1:1.

[0018] Another composition includes a network structure composed of strontium ions and polyphenol compounds, γ-PGA and ε-PLL, wherein γ-PGA and ε-PLL form a hydrogel in a weight ratio of 1:1. In SrC-MPNs@MN-PP, each milliliter of hydrogel contains 400μg to 500μg SrC-MPNs.

[0019] The microneedle patch of the present invention is prepared using a mold with a size of 200 μm×200 μm±500 μm (W×L×H) on which a 10×10 microneedle array is formed. The hydrogel formed by mixing SrC-MPNs and PP is loaded into the mold to form a medical device, which is conducive to the biologically active SrC-MPNs acting on the wound surface, accelerating the wound surface, especially the wound surface that is difficult to heal, such as: diabetic wound repair.

[0020] It has been verified that SrC-MPNs@MN-PP has both certain mechanical strength and the ability to deliver sustained-release drugs with minimal trauma. It is hygroscopic and can absorb excess tissue permeate from the wound surface and cover the wound surface until the wound heals, isolating the wound from the external environment. SrC-MPNs@MN-PP continuously releases SrC-MPNs, allowing these substances to be dissolved and absorbed into the tissue fluid around the wound, so that the strontium ions and chlorogenic acid in SrC-MPN can stably and continuously exert antibacterial and antioxidant properties, promote angiogenesis and promote wound healing. The results of in vivo experiments show that SrC-MPNs@MN-PP promotes wound healing in vivo and in vitro, promotes M2 macrophage polarization, removes excessive ROS, promotes angiogenesis and tissue regeneration, and promotes the healing of diabetic wounds. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 : is a diagram of the synthesis and characterization results of SrC-MPNs; wherein, a is a schematic diagram of the synthesis of SrC-MPNs microspheres, b is a FE-SEM image of the formation process of SrC-MPN, c is a SEM image and elemental map of the prepared SrC-MPNs, d is an X-ray diffraction (XRD) spectrum of SrC-MPNs powder, e is an absorption spectrum of Sr, CGA and SrC-MPNs from bottom to top, and f is a diagram of the cell viability results of HUVECs treated with SrC-MPNs at various concentrations of 0μg / mL, 50μg / mL, 100μg / mL, 200μg / mL, 300μg / mL and 400μg / mL for 48 hours;

[0022] Figure 2The synthesis and characterization results of SrC-MPNs@MN-PP are shown in FIG. a is a schematic diagram of the synthesis of SrC-MPNs@MN-PP, b is a photo of a microneedle mold and the prepared SrC-MPNs@MN-PP, c) a compression mechanical property curve of SrC-MPNs@MN-PP, d is a SEM image of SrC-MPNs@MN-PP, and e is a fluorescence microscopic image of SrC-MPNs@MN-PP after moisture absorption at various time points (80% humidity chamber, room temperature);

[0023] Figure 3 Figure 2 is the result of SrC-MPNs@MN-PP in vitro antioxidant and M2 polarization induction and angiogenesis; wherein, a is the ROS (stained with DCFH-DA (green)) measurement result after Raw264.7 cells were treated with normal cell culture medium (Control), SrC MPNs (50 μg / mL, 100 μg / mL), LPS, SRC-MPNS@MN-PP or MN-PP extract for 24 hours, b is the statistical analysis result of ROS generation in each group corresponding to the image shown in a, c is the flow analysis result of ROS fluorescence staining of Raw264.7 cells after different treatments, d is the statistical result of ROS fluorescence staining corresponding to the image shown in c, e is the cell viability result of human dermal fibroblasts after treatment with normal cell culture medium (Control) and various concentrations of SrC-MPNs for 24 hours, and f is the junctions and nodes and tube lengths in each group. length), g is a representative fluorescence image of HUVECs incubated on the solidified Matrigel matrix for 6 h in various treatments, h is a RT-qPCR statistical graph of Arg-1 after 48 hours of various treatments, i is a RT-qPCR statistical graph of CD31 after 48 hours of various treatments, and j is a RT-qPCR statistical graph of VEGF after 48 hours of various treatments;

[0024] Figure 4 Figures 2 and 3 are the results of the in vitro biocompatibility, cell proliferation and migration effects of SrC-MPNs@MN-PP; wherein, a is a fluorescence microscope image of live / dead cell double staining of HUVECs cultured in normal cell culture medium (Control), cell culture medium containing SrC-MPNs (50 μg / mL and 100 μg / mL), SrC-MPNs@MN-PP extract (containing approximately 100 μg / mL) or MN-PP extract; b is a graph showing the migration results of fibroblasts evaluated by a cell migration assay after various treatments for 24 hours; c is a quantitative graph corresponding to the gap closure rate in each group shown in b; and d is a statistical graph of the cell OD values ​​of fibroblast activity after various treatments for 1 day, 3 days and 5 days;

[0025] Figure 5 The figure is a diagram of wound healing results in diabetic mice; a is a representative photo image of diabetic wounds with different treatments after 0, 3, 5, 7, 11, 15 and 17 days, and b is a quantitative result diagram of the healing rate of the injured area in each group;

[0026] Figure 6 Immunofluorescence staining of M1 polarization; a is a representative image of double staining of CD68 and iNOS in wound tissues of each group after 3, 7 and 17 days of treatment, and b is a quantitative result of quantifying CD68+ and iNOS+ cells in each group after 3, 7 and 17 days of treatment;

[0027] Figure 7 Immunofluorescence staining of M2 polarization; a is a representative image of double staining of CD68 and CD206 in wound tissues of each group after 3, 7 and 17 days of treatment, and b is a quantitative result of CD68+ and CD206+ cells in each group after 3, 7 and 17 days of treatment;

[0028] Figure 8 The results of SrC-MPNs@MN-PP promoting rat tissue regeneration, collagen fiber repair, cell proliferation and angiogenesis are shown in the figure; wherein, a is the H&E and Massons color results of the control wound tissue of the control group (Control), SrC-MPNs powder, MN-PP and SrC-MPNs@MN-PP groups after 17 days of treatment, b is the results of anti-CD31 (red), anti-Ki67 (green) immunofluorescence staining and DAPI (blue) staining of the dermis of each group; c is the statistical result of the cell proliferation rate of the wound tissue in each group, and d is the statistical result of the capillary density of the wound tissue in each group;

[0029] Fig. 9 Schematic diagram of the mechanism by which the SrC-MPNs@MN-PP of the present invention promotes the healing of burn wounds;

[0030] Fig.10 It is the absorption intensity fitting curve of SrC-MPNs at 334 nm at various concentrations;

[0031] Fig.11 Graph showing the results of the SrC-MPNs antibacterial experiment; wherein, a is a representative photograph of Staphylococcus aureus strains treated with SrC-MPNs of various concentrations, and b is a quantitative statistical result graph showing each group of bacterial colonies corresponding to the image presented in a. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is described in detail below with reference to the accompanying drawings. The embodiments of the present invention are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention is described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solution of the invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

[0033] Fig. 9 The following is a schematic diagram of the mechanism of promoting the healing of burn wounds based on SrC-MPNs in the following embodiments of the present invention. Fig. 9 As shown, the porous network structure formed by strontium and polyphenol compounds is loaded into the microneedle patch to form a chlorogenic acid-based strontium ion-supported microneedle patch (denoted as: SrC-MPNs@MN-PP), which is inserted into the dermis in a minimally invasive manner and slowly released to promote the healing of diabetic wounds.

[0034] The sources of the main materials used in the following embodiments of the present invention are as follows:

[0035] γ-PGA (Mw = 1000 kDa) was purchased from Saitaisi Biotechnology Co., Ltd.;

[0036] ε-PLL (Mw = 2000-5000) was purchased from Aladdin (China);

[0037] Chlorogenic acid (CGA) with a purity of 98% was purchased from Tianjin Xiensi Biochemical Technology Co., Ltd.;

[0038] The microneedle patch mold was made of polydimethylsiloxane (PDMS), and each microneedle patch had a 10 × 10 array with a size of 200 μm × 200 μm ± 500 μm (W × L × H), purchased from Micropoint Technologies Ltd., Singapore;

[0039] High-glucose DMEM cell culture medium and fetal bovine serum were purchased from Gibco, UK;

[0040] Cell lines such as fibroblasts, HUVECs and Raw264.7 cells were cultured in a complete medium (high-glucose DMEM cell culture medium containing 10% FBS and 1% penicillin-streptomycin) in an incubator (37°C, 5% CO2).

[0041] The various test methods used in the following examples of the present invention are specifically described as follows:

[0042] 1) Preparation of SrC-MPN and SrC-MPNs@MN-PP:

[0043] Preparation of SrC-MPNs powder: SrC-MPNs were synthesized by solvothermal method. First, 100 mg Sr(NO3)2 and 380 mg chlorogenic acid were added to a round-bottom flask filled with 20 mL of water and stirred until uniform. Then, the pH was adjusted to 7 with 10 mol / L NaOH solution, and the mixed solution was heated in a 75 ° C water bath for 24 hours. After that, the white solid was separated in a centrifuge (12000 rpm, 15 minutes, 4 ° C) and washed twice with H2O. Finally, it was dried, ground and collected in EP tubes for storage.

[0044] Preparation of SrC-MPNs@MN-PP microneedles: First, prepare a 10wt% γ-PGA and 10wt% ε-PLL aqueous solution. Then mix the two into a translucent γ-PGA / ε-PLL(PP) hydrogel in a centrifuge (3000rpm, 2 minutes) and pour out the liquid. Add an appropriate amount of SrC-MPNs to the γ-PGA / ε-PLL(PP) hydrogel and stir until completely dispersed. Add the SrC-MPNs-loaded γ-PGA / ε-PLL(PP) hydrogel to the microneedle model and centrifuge at 3000rpm for 5min to ensure that the solution fully fills the tip of the microneedle model, and then place it in a 40°C dryer. After 12 hours, the microneedles were cured and demolded to obtain SrC-MPNs@MN-PP.

[0045] 2) Characterization of SrC-MPNs

[0046] SrC-MPNs were dissolved in DMSO with an absorbance of 334 nm. Then, a SrC-MPNs (10 μg / mL to 100 μg / mL) solution was prepared and measured at a wavelength of 334 nm to obtain a standard curve.

[0047] 3) Antibacterial activity of SrC-MPNs

[0048] Antimicrobial drugs were counted using the plate count method. First, a certain dose of Staphylococcus aureus was inoculated with an inoculation loop and diluted with sterile water to a colony forming unit (CFU) mL -1 of 10 6 times. Then, a solution of SrC-MPNs (500 μg / mL to 1000 μg / mL) was prepared, and 10 μl of completely diluted Staphylococcus aureus was added to 1 mL of SrC-MPNs (500 μg / mL to 10000 μg / mL) solution and sterile water (control group). After culturing in a 37°C incubator for 24 hours, 100 μl of the suspension was applied to Luria Bertani AGAR (LB AGAR) from different treatment groups and the plates were evenly coated. Finally, photos were taken and quantified after culturing in a 37°C incubator for 24 hours.

[0049] 4) CCK-8 detection of SrC-MPNs

[0050] CCK-8 kit (Dojindo Molecular Technologies, Rockville, MD, USA) was used to evaluate cell viability. HUVECs were seeded in 96-well plates with 5000 cells per well and maintained in DMEM medium containing 10% FBS. Different concentrations of SrC-MPNs (50, 100, 200, 300, 400 μg / mL) were co-cultured with HUVEs cells for 48 h, with 3 parallel culture media in each group, and normal culture media was used as the control group. After 48 h, 10% CCK-8 solution and culture medium were added to each well to stain the living cells. The cells were then placed in an incubator for 2 h (5%, CO2, 37°C). Finally, the 96-well plates were analyzed using SpectraMAX iD3 (Molecular Equipment Company, LLC, USA), and the results were statistically analyzed and plotted.

[0051] 5) Mechanical properties of microneedle patches

[0052] A displacement force test bench (dynamometer) was used to test the mechanical properties of the microneedle patch. Briefly, a single microneedle patch was placed vertically on a stainless steel platform (with the tip facing up), and the test bench sensor probe was moved at a speed of 0.1 mm s -1 The sensor was placed vertically near the microneedle at a speed of 1.000 m / s. The initial distance between the sensor and the microneedle tip was 1 cm. Displacement and force measurements began when the sensor first touched the microneedle tip and continued until the sensor moved 0.4 mm from the microneedle tip to the back of the patch. The results were then statistically analyzed and plotted.

[0053] 6) Hygroscopicity test

[0054] Sampled FITC and γ-PGA / ε-PLL (PP) hydrogel were mixed with SrC-MPNs until homogeneous to make microneedle patches. The dried SrC-MPNs@MN-PP were then placed in an airtight jar with a humidity of 80%. The MN patches were weighed at (1 h, 1.5 h, 2 h, 2.5 h, and 3 h) and photographed with a confocal microscope (Leica SP5, Leica Camera AG, Germany).

[0055] 7) In vitro antioxidants and M2 polarization induction

[0056] First, RAW264.7 cells (70×10 4Cells / well) were seeded on six-well plates. After culturing for 24 hours under typical conditions, the cells were exposed to 10μg / mL LPS. Various concentrations of SrC-MPNs (50μg / mL, 100μg / mL) or MN-PP extracts or SrC-MPNs@MN-PP (including 100μg / mL SrC-MPNs) were cultured for 24 hours, and groups without LPS or LPS alone were used as controls. Raw264.7 cells were stained with a ROS kit (Beyotime, China) according to the manufacturer's protocol. The stained cells were photographed using a fluorescence microscope. The differently treated cells were collected and dispersed in PBS and then analyzed by flow cytometry (Beckman-Colter, USA).

[0057] The antioxidant effect of SrC-MPNs was further verified. Through the protective effect on cells in a high concentration H2O2 environment. Fibroblasts (5000 cells per well) were seeded into 96-well plates and cultured for 24 hours. The cells were exposed to 300mM H2O2 and cultured for 30 minutes without treatment or with different concentrations of SrC-MPNs (50, 200, 300 and 400μg / mL). The untreated group was used as a control group. The CCK-8 kit was used to determine the cell viability of fibroblasts after various antioxidant treatments.

[0058] Finally, Raw264.7 cells were co-cultured with different treatment groups for 48 h, and mRNA from different treatment groups was extracted for RT-qPCR analysis. The expression of Arg-1 gene was identified. GAPDH was used as a housekeeping gene.

[0059] 8) Live / dead cell double staining

[0060] HUVEC were seeded at approximately 30 × 10 4 The cells were placed in a six-well plate with 100 cells and attached to the wall. The different treatment groups were added to the well plate and cultured for 48 hours. Then, 300 μL of CALCIN-AM / PI solution was added to each well according to the manufacturer's instructions. Incubate at 37°C with 5% CO2 for 15 minutes. A confocal microscope (Leica SP5, Leica Camera AG, Germany) was used to photograph the cells of different groups and record representative images.

[0061] 9) Microtubule formation analysis

[0062] First, 50 μL of growth factor-reduced matrix (BD Biosciences, USA) was added to each well of a 96-well plate and placed in an incubator for 30 minutes until solidified. 4Cells were inoculated on solidified Matrigel matrix, and different treatment groups were added to serum-free DMEM medium for culture. At 6 hours, each group of cells was stained with CALCIN-AM / PI solution, and representative images of each group were taken.

[0063] 10) CCK-8 assay for SrC-MPNs@MN-PP

[0064] A piece of MN-PP and SrC-MPNs@MN-PP was soaked in 5 mL PBS for 3 days to obtain extracts and prepare SrC-MPNs at different concentrations (50 μg / mL and 100 μg / mL). Fibroblasts were seeded in 96-well plates with 1500 cells per well and divided into 5 groups. After the cells attached to the wall, different treatment groups were added for co-culture. Complete medium containing 10% CCK-8 solution was added to each well on days 1, 3, and 5 to interact with living cells. After culturing in an incubator for 2 hours, the 96-well plate was analyzed with SpectraMAX iD3 (Molecular Equipment Company, LLC, USA), and the results were statistically analyzed and plotted.

[0065] 11) In vitro migration analysis

[0066] Fibroblasts were seeded in six-well plates and cultured in high-glucose DMEM medium supplemented with 1% fetal bovine serum. When the cell density in the culture dish reached 90% or more, a straight line was drawn in the center of the six-well plate with a 200 μL sterile pipette tip, and the detached cells were then washed with PBS and co-cultured with different treatment groups. Microscope images and quantitative measurements were taken at 0 h, 6 h, 12 h, and 24 h after treatment.

[0067] 12) Establishment of diabetic wound model and wound healing effect test of Chinese medicine compound preparation SrC-MPNs@MN-PP

[0068] A chronic wound model was established in 8-week-old diabetic (db / db) mice (Nanjing University-Nanjing Institute of Biomedical Sciences, China). After the mice were anesthetized and shaved, a circular wound with a diameter of 6 mm was formed on the back of each mouse. Subsequently, 48 mice were randomly assigned to different treatments (control group, SrC-MPNs powder, MN-PP, and SrC-MPNs@MN-PP). Different treatment regimens were used for the wounds. The mice were kept in individual cages with sufficient food and water. Wound images were taken at 0, 3, 5, 7, 11, 15, and 17 days after treatment.

[0069] 13) In vivo wound healing and macrophage polarization analysis

[0070] After 3, 7, and 17 days of treatment, mice were killed with an overdose of 4% chloral salt. First, the skin tissue of the wound was immersed in 4% paraformaldehyde for 24 hours, then embedded in wax blocks and sectioned at 5 μm for subsequent staining. The wound healing process was detected by hematoxylin-eosin (H&E), Masson's trichrome staining, and immunofluorescence staining with anti-CD31 (1:500) and anti-Ki67 (1:5000) antibodies. Macrophage polarization was detected using CD68, CD206, and iNOS antibodies.

[0071] 14) Statistical analysis

[0072] Statistical analysis was performed using GraphPad Prism 8.2.0 (GraphPad Software, USA). All statistical data are presented as mean ± SD, n = 3 per group. Ordinary one-way ANOVA and Turkish test were used to calculate p values. * indicates p < 0.05, ** indicates p < 0.01, *** indicates p < 0.001, and *** indicates p < 0.001 were considered statistically significant.

[0073] Example 1 Synthesis and Characterization of SrC-MPNs

[0074] When exposed to light and heat, polyphenols tend to lose their bioactivity. At pH = 7, chlorogenic acid and strontium ions self-assembled into SrC-MPNs ( Figure 1 a). Scanning electron microscopy shows the self-assembly process of SrC-MPNs from a monolithic structure to a uniform spherical structure with a diameter of about 100 μm ( Figure 1 b).

[0075] To verify the successful synthesis of SrC-MPNs, elemental mapping analysis was performed by SEM scanning to determine the composition of SrC-MPNs. The results showed that the elements C, O, and Sr were uniformly distributed in SrC-MPNs ( Figure 1 c). In order to further verify the synthesis of SrC-MPNs, powder synthesis of SrC-MPNs was carried out at 25°C, 50°C and 75°C. It was found that the colors of SrC-MPNs synthesized at different temperatures were different, and X-ray diffraction (XRD) detection was carried out. The results showed that at three different temperatures, there were special peaks at the same position, and the peaks increased with increasing temperature, indicating the integrity of the crystal structure of SrC-MPNs ( Figure 1 d).

[0076] In addition, the absorption peaks of CGA and SrC-MPN appeared simultaneously at 334 nm ( Figure 1 e and Fig.10), the peak shapes of the two are similar, but the peaks are displaced and completely overlap, so we believe that this is the effect of metal ions. Fig.11 a and Fig.11 As shown in b, after SrC-MPNs (500 μg / mL, 1 mg / mL) and sterile water were treated, the colony count of Staphylococcus aureus gradually decreased, indicating that SrC-MPNs have antibacterial effects. When the concentration of SrC-MPNs reached 300 μg / mL, there was no significant cytotoxicity to HUVECs ( Figure 1 f). SrC-MPNs were synthesized based on previous studies. SrC-MPNs retain the biological activity of chlorogenic acid and have the advantages of special structure, good stability and good biocompatibility.

[0077] Example 2 Synthesis and characterization of SrC-MPNs@MN-PP

[0078] In order to better treat diabetic wounds, drugs need to be effectively delivered to the skin. Ideally, a dressing with certain mechanical strength and good solubility is required. Since γ-PGA is a negatively charged acidic polymer and ε-PLL is a positively charged basic polymer, an adherent hydrogel γ-PGA / ε-PLL (PP) was obtained through physical interactions between ions. SrC-MPNs and PP hydrogels were physically crosslinked SrC-MPNs@MN-PP( Figure 2 a) was prepared using a commercial polydimethylsiloxane (PDMS) MN mold. Figure 2 b is a photo of the microneedle mold (left) and the prepared SrC-MPNs@MN-PP (right). The microneedle patch consists of a 10×10 microneedle (MN) array. By testing the compression mechanics of MN, it was found that MN has mechanical strength through the epidermal structure ( Figure 2 c). In addition, SEM scanning showed that SrC-MPNs@MN-PP had a pyramidal shape with sharp tips and were orderly arranged with the same size spacing, ensuring that SrC-MPNs@MN-PP could penetrate deep into the skin and release drugs to promote wound healing.

[0079] The fluorescence microscopy images of SrC-MPNs@MN-PP were further investigated. When SrC-MPNs@MN-PP was placed in a closed container with a humidity of 80%, Figure 2 e. SrC-MPNs@MN-PP was found to have a slower dissolution rate. By inserting the SrC-MPNs@MN-PP patch into the back wound of mice, the MN melted and remained on the wound surface until the wound healed and fell off, as shown in Figure 5 As shown in a.

[0080] The above results show that the SrC-MPNs@MN-PP patch has good hygroscopicity and can absorb excess tissue exudate produced by the wound, providing a good environment for wound healing. MN can be applied to the wound surface like a clinical dressing to isolate the wound from the external environment and accelerate wound healing. SrC-MPNs@MN-PP can be used as an effective drug delivery system with good mechanical strength, good hygroscopicity and isolation.

[0081] Example 3 In vitro angiogenesis-promoting ability of SrC-MPNs@MN-PP

[0082] Studies have shown that angiogenesis is essential for diabetic wound healing. Some chemokines, such as VEGF and CD31, have been shown to play an important role in angiogenesis. In this example, the effect of SrC-MPNs on in vitro angiogenesis, which requires blood supply for wound healing, was investigated. Different therapeutic extracts were co-cultured with endothelial cells for 6 hours, and normal cell culture medium was used as a control. The results showed that the SrC-MPNs@MN-PP extract composition had the most obvious effect, such as Figure 3 As shown in g.

[0083] Quantification of connection points, nodes and pipe lengths ( Figure 3 f), the results showed that SrC-MPNs@MN-PP had significant differences compared with the control group. To further verify the role of SrC-MPNs@MN-PP in promoting tube formation, real-time RT-qPCR was performed, and the mRNA levels of vascular biomarkers (CD31 and VEGF) were detected by RT-q polymerase chain reaction ( Figure 3 i and Figure 3 j) The SrC-MPNs@MN-PP extract-treated group significantly increased VEGF expression compared with the control group, but it was not statistically significant. In conclusion, the use of SrC-MPNs@MN-PP for angiogenesis in vitro has been demonstrated and is expected to be effective for angiogenesis in vivo.

[0084] Example 4 In vitro biocompatibility, cell proliferation and migration effects of SrC-MPNs@MN-PP

[0085] Under ideal conditions, the dressing not only has a therapeutic effect, but also has good biocompatibility and low cytotoxicity. This example verifies that various concentrations of SrC-MPNs, MN-PP, and SrC-MPNs@MN-PP extracts were co-cultured with endothelial cells, and normal culture medium was used as a control for live / dead cell staining ( Figure 4a). The results showed that the materials were biocompatible and non-cytotoxic. The effects of the extracts of SrC-MPNs, MN-PP and SrC-MPNs@MN-PP at different concentrations on cell proliferation and migration were evaluated by scratch test. The results showed that compared with the untreated group, the other treated groups had enhanced effects on cell migration and proliferation ( Figure 4 b) If Figure 4 As shown in (c), quantitative analysis showed that SrC-MPNs@MN-PP had the most significant cell migration and proliferation. In conclusion, SrC-MPNs@MN-PP had good in vitro biocompatibility and promoted cell proliferation and migration.

[0086] To further verify the biocompatibility of the material, CCK-8 was used to measure the absorbance OD values ​​of fibroblasts on days 1, 3, and 5. Figure 4 As shown in Figure d, compared with the control group, the OD values ​​of the different treatment groups increased significantly on the first day, and there were significant differences, indicating that the different treatment groups had no cytotoxicity and promoted cell proliferation. The OD values ​​of each group continued to increase with the extension of culture time, and there was no significant difference compared with the control group.

[0087] Example 5 Evaluation of wound healing in diabetic mice

[0088] The in vivo wound healing of SrC-MPNs@MN-PP was further verified on live diabetic mice with skin wounds. A mouse model was first established by creating a 6 mm circular wound (db / db) on the back of diabetic mice. After surgery, all mice were randomly divided into 4 groups and given PBS (control group), SrC-MPNs powder, MN-PP, and SrC-MPNs@MN-PP, respectively. The wound healing status was recorded over time, and photographic images of the mouse wounds under different treatments were taken at 0, 3, 5, 7, 11, 15, and 17 days ( Figure 5 a). The results showed that during the wound healing process, the microneedles gradually melted and were applied to the wound until the scab healed. On day 17, most of the SrC-MPNs@MN-PP treatment group was healed, while the other groups were not completely healed. The percentage of wound area at different days was quantified ( Figure 5 b). The wound healing area of ​​the treatment group was better than that of the control group, but there was a more significant difference between the two groups in promoting wound healing in SrC-MPNs@MN-PP.

[0089] Example 6 Verification of SrC-MPNs@MN-PP inducing M2 repolarization in vivo

[0090] Macrophages are key regulators of wound healing and can switch from an active pro-inflammatory or "M1" phenotype to a pro-healing or "M2" phenotype, depending on the stage of wound healing, to ensure proper wound healing. In vivo immunofluorescence staining of macrophage markers (CD68, red), M1 macrophage markers, and M2 macrophage markers was performed on wound tissues from each treatment group.

[0091] Typically, M1 macrophages are the predominant phenotype during the first three days after injury, whereas M2 macrophages typically peak on day 7 after injury. Representative images of CD68 / iNOS dual staining on day 3 ( Figure 6 a) and quantification of CD68+iNOS+ cell numbers ( Figure 6 b) shows that compared with the control group, SrC-MPNs powder, MN-PP and SrC-MPNs@MN-PP treatments reduced M1 polarization by 2.44, 1.60 and 2.87 times, respectively. SrC-MPNs@MN-PP was also 1.18 times lower than SrC-MPNs powder ( Figure 6 b). On the 7th day, compared with the control group, the SrC-MPNs powder, MN-PP and SrC-MPNs@MN-PP groups continued to decrease by 2.77 times, 1.77 times and 3.70 times, respectively. SrC-MPNs@MN-PP also decreased by 1.34 times compared with SrC-MPNs powder ( Figure 6 b). In addition, on day 17, the SrC-MPNs powder, MN-PP, and SrC-MPNs@MN-PP groups also decreased by 1.93, 1.71, and 2.18 times, respectively ( Figure 6 b). SrC-MPNs@MN-PP also decreased by 1.34 times compared with SrC-MPNs powder. Overall, it has been demonstrated that M1 macrophages decreased in the treatment groups compared with the control group, but this was more prominent in the SrC-MPNs@MN-PP group.

[0092] Next, M2 repolarizes ( Figure 7 a) CD68 / CD206 double staining was used for analysis. The results showed that compared with the control group, the SrC-MPNs powder, MN-PP and SrC-MPNs@MN-PP groups increased by 2.79 times, 3.38 times and 5.90 times on the third day, respectively ( Figure 7 b). SrC-MPNs@MN-PP increased by 2.11 times compared with SrC-MPNs powder. On the 7th day, the SrC-MPNs powder, MN-PP and SrC-MPNs@MN-PP groups increased by 1.78, 1.60 and 2.18 times, respectively, and SrC-MPNs@MN-PP increased by 1.23 times compared with SrC-MPNs powder ( Figure 7b). On the 17th day, the repolarization of SrC-MPNs powder, MN-PP and SrC-MPNs@MN-PP was the same, 1.45 times, 1.46 times and 1.91 times, respectively, and SrC-MPNs@MN-PP was 1.31 times that of SrC-MPNs powder ( Figure 7 b). In conclusion, the treatment groups promoted M2 repolarization in vivo, but the effect was more significant in the SrC-MPN@MN-PP treatment group compared with the single drug treatment group.

[0093] Thus, the SrC-MPNs@MN-PP group reduced M1 polarization and promoted M2 repolarization in vivo, thereby promoting wound healing.

[0094] Example 7 Verification of the efficacy of SrC-MPNs@MN-PP in rat tissue regeneration, collagen fiber repair, cell proliferation and angiogenesis

[0095] First, H&E staining was used to observe the formation of granulation tissue, measure tissue levels, and observe the process of epithelial repair ( Figure 8 a, row 1). The staining results at day 17 showed that granulation tissue had been completely formed in the SrC-MPNs@MN-PP group. The epithelial tissues in the control group and other treatment groups did not heal completely, as shown by the arrows in the figure. In addition, Masson trichrome staining was used to stain the collagen fibers in animal tissues blue, the muscle fibers red, and the cell nuclei blue, thereby detecting and distinguishing collagen fibers from muscle fibers ( Figure 8 a, row 2). The SrC-MPNs@MN-PP group had the best tissue collagen deposition and orientation, indicating better wound healing and tissue remodeling.

[0096] Secondly, tissue regeneration was observed by immunofluorescence staining, and CD31 and Ki67 were used to mark cell proliferation and capillary formation after different treatments, respectively ( Figure 8 b). Quantification of the density of regenerating capillaries and the number of regenerating cells ( Figure 8 c and Figure 8 d). The results showed that the SrC-MPNs powder, MN-PP, and SrC-MPNs@MN-PP groups increased by 1.20 times, 1.19 times, and 1.70 times, respectively, compared with the control group. SrC-MPNs@MN-PP was 1.36 times that of SrC-MPNs powder. In addition, by quantifying the number of regenerative cells, the SrC-MPNs powder, MN-PP, and SrC-MPNs@MN-PP groups increased by 1.79, 2.22, and 2.80 times, respectively, compared with the control group. The content of the SrC-MPNs@MN-PP group was 1.56 times that of SrC-MPNs powder.

[0097] In conclusion, SrC-MPNs@MN-PP significantly promoted tissue regeneration in vivo and enhanced wound healing, tissue regeneration, and angiogenesis compared with the control group or single-drug treatment groups.

Claims

1. A composition, characterized in that It is composed of strontium ions and chlorogenic acid in a network structure. By weight, the ratio of strontium ions to chlorogenic acid is 1:9-11.

2. The composition according to claim 1, characterized in that It is prepared from Sr(NO3)2 and chlorogenic acid by hydrothermal method.

3. The composition according to claim 2, characterized in that Dissolve Sr(NO3)2 and chlorogenic acid in water, stir until uniform, adjust pH to 7, place in a 75°C water bath for several hours, and centrifuge to obtain the product.

4. The composition according to claim 1, characterized in that Also included are hydrogels.

5. The composition according to claim 4, characterized in that The hydrogel is selected from one or more of PEG, PLGA-PEG, γ-PGA, ε-PLL, hyaluronic acid, gelatin, chondroitin sulfate and cross-linked modified derivatives thereof.

6. The composition according to claim 4, characterized in that The hydrogel consists of gamma-PGA and epsilon-PLL, and the weight ratio of gamma-PGA to epsilon-PLL is 1:

1.

7. The composition according to claim 6, characterized in that Each milliliter of the hydrogel contains 400 μg to 500 μg of SrC-MPNs.

8. Use of the composition according to claim 1 in preparing medical devices for diabetic wound repair.

9. A medical device, characterized in that The invention comprises the composition according to claim 1.

10. The medical device according to claim 9, characterized in that The medical device is a microneedle, including a 10×10 microneedle array, which is made of a mold with a size of 200μm×200μm±500μm.

Citation Information

Cited By

  • Phenolic acid-strontium nanoparticles as well as preparation method and application thereof

    CN121265634A

  • Preparation method and application of strontium ion cross-linked multifunctional hydrogel material with immunoregulation characteristic

    CN121927112A